2019
DOI: 10.11591/ijere.v8i3.20243
|View full text |Cite
|
Sign up to set email alerts
|

Using problem-based learning in college: Mastery concepts subject statistical sesearch and motivation

Abstract: <span>Based on the problems obtained, the ability of students to master the subjects of research statistics is still categorized as low until this causes them to be weak in completing their final assignments. Therefore, the researchers investigated how students' mastery of the research statistical concepts and their learning motivation using learning innovations, one of which was Problem Based Learning (PBL). This research was conducted at the Islamic Education School (PGMI) Islamic State Teacher Educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…These results also showed that Gengobot is effective as a medium for learning Japanese (Xiaoxu & Yoshino, 2011;Stockwell & Hubbard, 2013;Haristiani et al, 2019;. The use of the MALL concept and the features in Gengobot which are new and interesting make users more motivated in learning Japanese (Chuang, 2014;Ediansyah et al, 2019), and also because the application is practical and easy to use (Hasan et al, 2020;Keezhatta & Omar, 2019;Kondo et al, 2012). The material in the application is also suitable for the targeted level of learners and easy to understand (Haristiani et al, 2019;.…”
Section: The Implementation Of Gengobot Applicationmentioning
confidence: 92%
“…These results also showed that Gengobot is effective as a medium for learning Japanese (Xiaoxu & Yoshino, 2011;Stockwell & Hubbard, 2013;Haristiani et al, 2019;. The use of the MALL concept and the features in Gengobot which are new and interesting make users more motivated in learning Japanese (Chuang, 2014;Ediansyah et al, 2019), and also because the application is practical and easy to use (Hasan et al, 2020;Keezhatta & Omar, 2019;Kondo et al, 2012). The material in the application is also suitable for the targeted level of learners and easy to understand (Haristiani et al, 2019;.…”
Section: The Implementation Of Gengobot Applicationmentioning
confidence: 92%
“…The novelty of this study is to define science process skills integrated education students Physics in Universitas Jambi by reviewing eight aspects (identifying variables, arranging graphs, obtaining and processing of data, analyzing investigations, making a hypothesis, defining variables operationally, designing investigation, and experimenting) experimenter material reflection on a flat mirror in the laboratory. Physics investigations by the way that students acquire the experimental data, by observing and decide what tools need to be used, and make hypotheses [21].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that similar innovations can improve the capacity of teachers and aspiring teachers to establish a more engaging and adaptable learning environment. Prospective instructors will be provided with sophisticated materials and methodologies to create an engaging and interactive learning environment for their pupils (Ediansyah et al, 2019;Sholikah & Harsono, 2021;J. Zhang, 2010).…”
Section: Introductionmentioning
confidence: 99%